Odour impact assessment handbook - Naddeo, V.; Belgiorno, V.; Zarra, T. (Chichester, West Sussex, United Kingdom ; Hoboken : John Wiley & Sons, 2013)
Odours have become a priority concern for facility operators, engineers and urban planners who deal with waste and industrial treatment plants. The subjectivity of smell perception, its variability due to frequency and weather conditions, and the complex nature of the substances involved, has long hampered the regulation of odour emissions. This book provides a comprehensive framework for the assessment, measurement and monitoring of odour emissions, and covers: Odour characterization and exposure effectsInstruments and methods for sampling and measurement<li.
5 Dispersion Modelling for Odour Exposure Assessment5.1 Introduction; 5.2 Odour Perception; 5.2.1 Odour Intensity; 5.2.2 Temporal Dimension; 5.3 Overview on Types of Odour Dispersion Model; 5.4 Algorithms to Estimate Short-Term Odour Concentrations; 5.5 Annoyance; 5.6 Odour Impact Criteria for Use in Dispersion Modelling; 5.7 Meteorological Input to Odour Dispersion Models; 5.7.1 Wind Information; 5.7.2 Information on Atmospheric Stability; 5.7.3 Information on the Mixing Height; 5.8 Evaluation of Odour Dispersion Models; References; 6 Odour Regulation and Policies; 6.1 Introduction.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Odor control -- Handbooks, manuals, etc; Volatile organic compounds -- Environmental aspects -- Handbooks, manuals, etc; Air quality management -- Handbooks, manuals, etc; Air quality management; Odor control; Volatile organic compounds -- Environmental aspects; TECHNOLOGY & ENGINEERING -- Environmental -- Pollution Control; Air quality management; Odor control; Volatile organic compounds -- Environmental aspects; Electronic books; Handbooks and manuals; Electronic books